Efficacy of a psico-geriatric program - Falcón Cermeño, Luz Kelly (2019)
This article will present evidence on the efficacy of the personal development program for elderly applied in a Geriatric Residential Center in Metropolitan Lima. The sample was comprised by 15 residents of both sexes whose age was between 65 to 87 years old. The Psychological wellbeing scale by Díaz, Rodríguez, Blanco, Moreno, Gallardo, Valle & Van Dierendonck was used as instrument (2006). The design of the investigation is quasi-experimental applied in two times before the implementation of the program and after the implementation of the program. The results evidenced that the areas of self-acceptance, positive relationships and life purpose generated significant changes in the residents of the center. Also, in the social-demographic variables of this study was concluded that male participants with complete secondary studies whose ages were form 65 to 87 years old obtained high levels of psychological wellbeing.